Saving Determinants Among Career Women In Private Sectors In Penang - Sulaiman, Nur Shazlina Haji Mohd (2019)
This study focuses on saving characteristics among career women in Penang. It is important to have a better understanding on the saving characteristics among women, in our case, career women in private sectors because studies indicate that women are likely to have lower income and wealth on average compared to men. As such, their livelihood after retirement may be jeopardized given the escalating prices of necessary items and healthcare expenses. This research analyze the saving characteristics which involves socio demographic comparisons and types of saving or investment instrument used by career women in Penang in order to save for their future. An identification of investment instruments, the level of savings and women’s tendency to save for the future and for rainy days will help them to prepare for the uncertainties that life has to offer. This is because women have lower rate of participation in retirement plans as compared to men and are more likely to be living in poverty during retirement. Findings from this study can be beneficial to many quarters apart from the women themselves because they are too dependent on their spouse in planning for their retirement. Saving characteristics such as types of saving, percentage of monthly saving and the tendency to save will be taken into consideration in analysing and having a better understanding on the saving characteristics of the career women. In this research quantitative method has been conducted. Questionnaires were distributed to women working in service and manufacturing industries which are the two most dominant industries in Penang.